2003
DOI: 10.1105/tpc.012559
|View full text |Cite
|
Sign up to set email alerts
|

Target Site Specificity of the Tos17 Retrotransposon Shows a Preference for Insertion within Genes and against Insertion in Retrotransposon-Rich Regions of the Genome

Abstract: Because retrotransposons are the major component of plant genomes, analysis of the target site selection of retrotransposons is important for understanding the structure and evolution of plant genomes. Here, we examined the target site specificity of the rice retrotransposon Tos17 , which can be activated by tissue culture. We have produced 47,196 Tos17-induced insertion mutants of rice. This mutant population carries ‫ف‬ 500,000 insertions. We analyzed Ͼ 42,000 flanking sequences of newly transposed Tos17 cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
443
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 477 publications
(455 citation statements)
references
References 36 publications
(44 reference statements)
10
443
0
2
Order By: Relevance
“…5), with at least one insertion detected in 3,243 genes. The density of Tos17 insertions is higher in euchromatic regions of the genome 30 , in contrast to the distribution of high-copy retrotransposons, which are more frequently found in pericentromeric regions. A similar target site preference has been reported for T-DNA insertions in Arabidopsis 31 .…”
Section: Centromere Locationmentioning
confidence: 76%
See 1 more Smart Citation
“…5), with at least one insertion detected in 3,243 genes. The density of Tos17 insertions is higher in euchromatic regions of the genome 30 , in contrast to the distribution of high-copy retrotransposons, which are more frequently found in pericentromeric regions. A similar target site preference has been reported for T-DNA insertions in Arabidopsis 31 .…”
Section: Centromere Locationmentioning
confidence: 76%
“…These features, together with its preferential insertion into gene-rich regions, make Tos17 uniquely suitable for the functional analysis of rice genes by gene disruption. About 50,000 Tos17-insertion lines carrying 500,000 insertions have been produced 30 . A total of 11,487 target loci were mapped on the 12 pseudomolecules ( Supplementary Fig.…”
Section: Centromere Locationmentioning
confidence: 99%
“…More and more studies show that TEs have a capacity for affecting adjacent genes by altering transcriptional regulation [44][45][46][47], and retrotransposon transcription has a key influence upon the transcriptional output of genome [48]. In this study, many different kinds and abundant numbers of TEs were identified in the pool of transcripts, which provided the evidence that these elements not only played key roles in the diversity of transcripts and the complexity of functional genome but also might contribute to the adaptation and tolerance to the environmental stress.…”
Section: Tes and Ssrsmentioning
confidence: 99%
“…A non-phototropic mutant ( cpt1 ) in the Nihonmasari background (Haga et al . 2005), a lazy mutant in the Kamenoo background (Goto 1978;Abe, Takahashi & Suge 1994) and retrotransposon Tos17 insertion lines in the Nipponbare background (Miyao et al . 2003) were also used.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%